EFFECTS OF PARENTS SEX ، BIRTH TYPE، AND AGE ON LIVABILITY OF TURKISH AWASSI SHEEP LAMBS. - ALI, MAAN A.; Taha, SADIK A.; KHALEEL, NAZAR I.; HADI, FINDYIA H. (Diyala Agricultural Sciences Journal, 2013)
Sheep records of Agricultural Research State Board - Sheep Station in Baghdad ، were analyzed ، which its accounts were 967 ،956 ، 951 ، 935 record for livability at weaning age، 6، 9، and 12 months of age respectively for the years 2009 ، 2010، 2011، in order to study the effects of parents sex،birth type، age،and interaction among these factors on lambs livability at weaning age to one year of age . Study results appeared that there was no significant effect of rams age on lambs livability at weaning age to one year of age. While ewes age effect was significant (p<0.05) on lambs livability at 6 ،9 months of age ،as it was highly significant (p<0.01) on lambs livability at one year of age ،but its effect was not significant on lambs livability at weaning age . Ewes with 4 years of age gave highest lambs livability at weaning age and at 6، 9،12 months of age which reached 96.92،96.92،96.51،95.41% respectively،while the lowest lambs livability were to ewes with 8 years of age ،which reached 83.33،75.00،75.00،66.66 % at weaning age،6،9،12 months of age respectively. Parents sex and their birth type effects were not significant on lambslivability at weaning age to one year of age as well as the interaction among these factors which was not significant on lambs livability.